(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The text is an experience report that deals with compositional elements in the collective creation process of the videodance Endless - or I forgot to remember, by the group Tatá, produced at a distance due to social isolation, in 2020. One element is corporal preparation: practices of production of body-world connection as a continuous space. Another element is the relationship of the performers-creators with the camera and its adaptation difficulties. The third element covered is video editing, focusing on transitions. The research identifies Endless’s composition as a transcreation. It shows the emergence of the presence dimension in the transcreation operation, recognized as the production of affections. It presents the notions of affection, infinite body and connection, which emerge from the experience of creation.